Design and psychometric validation of a social capital questionnaire for adults with end-stage chronic kidney disease undergoing dialysis or hemodialysis - Alicia Alanis-Ocádiz; Svetlana V. Doubova; José Manuel Arreola-Guerra; Adriana Monroy; Jannett Padilla-López; Carolina Quiñones-Villalobos; Carlos Alberto Prado-Aguilar (BMC Nephrology)
Abstract Background The effects of end-stage kidney disease (ESKD) can spill over into a patient’s social life. Social capital (SC) is a determinant of health that can enhance patients’ health through support and resources. However, no questionnaire is currently available to measure SC in ESKD patients. This study aimed to design and validate a questionnaire to measure SC in ESKD adults undergoing dialysis or hemodialysis. Methods A mixed methods approach was used to generate the questionnaire and determine its content validity with a panel of nine experts and content validity index, face validity through cognitive interviews with patients, construct validity (exploratory and confirmatory factor analysis), criterion validity, reliability and the effect of known groups differences. Results Content validity was confirmed by an expert panel, achieving a content validity index value > 0.85 for all items. Face validity was achieved through cognitive interviews with 20 patients over 18 years of age in a terminal stage of CKD, ensuring that the target population understood the questions. An exploratory factor analysis used the sample of 610 patients and tested the structure of the seven dimensions of the structural domain (participation in organizations, links to institutions, social network sizes, collective activities, diversity, bridging, and bonding) and explained 95.7% of the total variance with a reliability of 0.89, and criterion validity > 0.32 (p < 0.05) for the correlations between the indices of each dimension and the domain index. The structure of the cognitive domain was tested for six dimensions (norms of reciprocity, social harmony, feeling of belonging, perceived fairness, social support, and social trust) with a total variance of 80.7%, reliability of 0.94 and criterion validity for correlations > 0.68 (p < 0.05). The confirmatory factor analysis with 352 patients proved the factorial structure adequate for both questionnaire domains and all dimensions, with CFI and TLI values > 0.9, an RMSEA ≤ 0.06, and SRMR ≤ 0.05. Conclusions We conclude that the questionnaire designed to measure social capital is valid and reliable for ESKD patients in Mexico.